Anatomy of local government in Bangladesh - Ferdous, Jannatul; Razaul, Mohammad 1981- (Lexington Books, 2025)
"Anatomy of Local Government in Bangladesh provides a comprehensive analysis of Local Government Institutions (LGIs), focusing on their structure, functions, and challenges. The book delves into the historical evolution of municipal governance, financial autonomy issues, and the intricate relationship between local and national governments, contributing to informed policymaking and the advancement of local governance in Bangladesh"--
2412
Keywords: Local government / Bangladesh; Decentralization in government / Bangladesh; Bangladesh / Politics and government; Administration locale / Bangladesh; Bangladesh / Politique et gouvernement